Wound contraction and epithelisation effects of Acrostichum aureum L. in rabbits - Herman, Hendy Putra; Darnis, Deny Susanti; Saad, Shahbudin; Bakhtiar, M. Taher; Ramli, Norazsida (IIUM Press, 2022)
Introduction: Rhizomes paste from Acrostichum aureum Linné was used traditionally by Malays ethnic groups in Malaysia for wound healing treatment. To evaluate wound healing properties of aqueous and ethanolic extract of A. aureum on rabbits. Method: There were four treatments namely aqueous extracts of rhizomes, leaves and stems A. aureum with low and high dose (5 % and 10 %). There were four rabbits in three treatment groups with each rabbit were inflicted with excisional wounds on their back near the neck with 6 mm in diameter. Topical treatment was applied once daily until complete healing with Solcoseryl jelly served as positive control group and blank aqua cream served as negative control group. The percentage period of epithelisation and wound contraction were measured every 3 days interval. At day 15, all healed wound specimens were biopsied and stained with Masson’s trichrome staining for histopathological study. Results and Discussion: From the results, all extracts from A. aureum possessed tannins and total tannin content showed that ethanolic extracts had higher total tannin content compared to aqueous extracts. Based on percentage wound contraction and epithelisation period, the treatment with 5 % aqueous extracts of leaves A. aureum was the most effective wound healing agent in enhancing higher percentage wound contraction, rapid epithelisation period, producing more collagens and fibroblasts proliferation. Conclusion: It was suggested that wound healing properties of rhizomes and leaves A. aureum was contributed by its high total tannin content. This finding would be able to justify its traditional claim as wound healing treatment by Malays communities in Malaysia.